Mobile Travel Guide For Tourism - HUSEIN, Sukainah (Universiti Teknologi Petronas, 2007)
The number of local and foreign tourists worldwide has increased dramatically. However, services provided are always not enough to satisfY the tourists. Tourists will need an easy access providing them information at anytime, anywhere, with affordable price. To overcome this problem, Mobile Travel Guide for Tourism project was initiated. This system is using SMS as the user interface and it understands users' input with predetermined format as queries to access the database. Methodology that is practically adequate to be implemented in this system is Phased Development-based methodology. To compute directions to a place, the system is implementing Dijkstra algorithm which is efficient to find the shortest path. The system implementation is done through a wireless modem connected to a server that contains the database of all information. SMS Gateway is installed in the system to interface between the modem and the users' request database. At the end of the project, it is expected that the satisfactory level of tourism industry will be appreciating.